THE INFLUENCE OF SCHOOL ORGANIZATIONAL CLIMATE, WORK ENVIRONMENT AND JOB SATISFACTION ON TEACHER PERFORMANCE AT STATE JUNIOR HIGH SCHOOL KUTABLANG BIREUEN DISTRICT - Luthfi, Muhammad; Iba, Zainuddin (IndOmera, 2023)
This study aims to determine the factors that influence teacher performance in terms of aspects of school organizational climate, work environment and teacher satisfaction factors. This research is a survey using quantitative and associative descriptive methods with the object of research being teachers who work at SMP Negeri Kutablang Bireuen District. Data analysis in the framework of hypothesis testing through statistical inference with multiple regression analysis approach. The results of the study, it was found that; (1). (1). There is a partial significant effect of School Organizational Climate (SO), Work Environment (WE) and Teacher Job Satisfaction (TS) on Teacher Performance (TP), with the regression equation TP = 16.458 + 0.470 SO + 0.518 WE + 0.339 TS. (2). Simultaneously it is proven that the variables of school organizational climate, work environment and job satisfaction have a significant effect on performance with a contribution of 40.5%. While the remaining role of variables not examined was 59.5%, including motivation, work discipline, school culture, teacher competence, and others.